Offshore wave climate of the Pará-Maranhão Basin, Amazonian continental shelf - João Luiz B. Carvalho; Inaiê M. Miranda; Eduardo V. Queiroz; Juliana S. Guerreiro; Henrique, P. Pereira; Susana S. Vinzon (Ocean and Coastal Research)
This study assesses the offshore wave climate of the Pará-Maranhão Basin on the Amazonian continental shelf, a crucial region for its environmental and economic activities, including fishing and extractive activities, potential oil exploration, and complex landscape marked by extensive mangrove systems comprising protected areas and touristic coastal cities in an accelerated stage of development that face significant challenges with coastal erosion. Despite the region’s relevance, studies on wave climate are scarce. To address this gap, this research provides a detailed assessment of the offshore wave climate of the North Brazilian Coast, particularly the Pará-Maranhão sector. This quantitative assessment allowed a comprehensive characterization of the wave climate in the region. Such detailed understanding is essential for various stakeholders involved in coastal management, marine transportation and environmental protective initiatives. To do so, long-term (27-year) datasets of wave parameters (Hs, Tp, DirTp) were analyzed by bivariate histograms, using WAVERYS model, which after an in-depth comparison with ERA-5 and WW3 was found to represent local wave conditions most accurately. The study’s results also showed the greatest joint occurrence of waves is observed when peak periods vary between six and eight seconds, predominantly originating from the east-northeast (ENE) to the east-southeast (ESE) directions (local wind-generated waves associated with trade winds), accounted for approximately 41% of occurrences, with higher occurrences from E (25%). Additionally, waves with peak periods longer than 20 seconds predominantly originate from directions spanning north-northeast (NNE) to east-northeast (ENE) (swell waves from the Northern Hemisphere). Moreover, this study holds the promise for replication in other regions with similar data constraints and can contribute to the future implementation of a refraction-diffraction model, essential for the design of coastal infrastructures. Thus, subsidizing informed decision-making for sustainable coastal development in the Amazon littoral.